2021
DOI: 10.1038/s41380-021-01172-4
|View full text |Cite
|
Sign up to set email alerts
|

A Baldwin interpretation of adult hippocampal neurogenesis: from functional relevance to physiopathology

Abstract: Hippocampal adult neurogenesis has been associated to many cognitive, emotional, and behavioral functions and dysfunctions, and its status as a selected effect or an “appendix of the brain” has been debated. In this review, we propose to understand hippocampal neurogenesis as the process underlying the “Baldwin effect”, a particular situation in evolution where fitness does not rely on the natural selection of genetic traits, but on “ontogenetic adaptation” to a changing environment. This supports the view tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 224 publications
(272 reference statements)
1
15
0
Order By: Relevance
“…In addition, we have recently observed that the suppression of Rnd2 , a small Rho GTPase, in DGNs born in neonates (P1) has no effect on anxiety-like behaviour whereas its deletion in Adu-DGNs exacerbates anxiety-like behaviours [ 38 ]. Based on this data we suggest that neurogenesis is a “Baldwin mechanism” that allows “ontogenetic adaptation” to a changing environment [ 39 ]. Given this framework, deleterious life events (such as chronic stress, drugs and a high-fat diet) during perinatal life and adolescence may have different outcomes and are likely to induce a vulnerable state that conditions the occurrence of disorders later in life [ 40 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have recently observed that the suppression of Rnd2 , a small Rho GTPase, in DGNs born in neonates (P1) has no effect on anxiety-like behaviour whereas its deletion in Adu-DGNs exacerbates anxiety-like behaviours [ 38 ]. Based on this data we suggest that neurogenesis is a “Baldwin mechanism” that allows “ontogenetic adaptation” to a changing environment [ 39 ]. Given this framework, deleterious life events (such as chronic stress, drugs and a high-fat diet) during perinatal life and adolescence may have different outcomes and are likely to induce a vulnerable state that conditions the occurrence of disorders later in life [ 40 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reversal learning protocol urges animals to form allocentric navigation strategies given that they have to learn the current positional relation between the distal visual cues around the pool and the new platform location ( Anacker and Hen, 2017 ). After applying the reversal learning protocol, research groups have shown that rodents with reduced neurogenesis are unable to efficiently learn the new platform location ( Dupret et al, 2008 ; Farioli-Vecchioli et al, 2008 ; Zhang et al, 2008 ; Garthe et al, 2009 , 2016 ; for a discussion see Anacker and Hen, 2017 ; Abrous et al, 2021 ). In this case, rodents show prolonged times searching over the old platform location, a search pattern called perseverance.…”
Section: The Morris Water Mazementioning
confidence: 99%
“…Adult neurogenesis has been widely associated with anxiety-related behaviors and spatial learning and memory capabilities (Snyder and Drew, 2020 ; Abrous et al, 2021 ) so we analyzed the consequences of Vangl2 mutation on both affective and cognitive functions. Contrary to our expectations in light of their reduced neurogenesis, we did not evidence any deficit in measures of anxiety in looptail mice.…”
Section: Discussionmentioning
confidence: 99%